Effect of laser therapy on healing in patients with Diabetes mellitus: literature review (Research, Society and Development, 2023)
Wound healing in individuals with diabetes mellitus is a complex and often compromised process due to factors such as decreased blood supply, peripheral neuropathy, and impaired immune system. This article aims to review the existing literature on the effect of laser therapy on healing in patients with diabetes mellitus. The methodology used consisted of a literature review, with search in electronic databases, such as SCIELO, LILACS and MEDLINE. The Boolean operator "and" was used, to locate the studies the following descriptors in health science (DeCS) were used: Healing, diabetes mellitus, laser therapy, diabetic foot. Randomized controlled trials evaluating the effect of laser therapy on wound healing in patients with diabetes mellitus were included. The results of the review showed consistent evidence that laser therapy may be beneficial for wound healing in patients with diabetes mellitus. Low-intensity laser stimulation has been shown to promote angiogenesis, increase collagen synthesis, accelerate reepithelialization, and reduce local inflammation. Thus, laser therapy has been shown to be effective in reducing pain and improving patients' quality of life. Based on the studies reviewed, it is concluded that laser therapy is a promising therapeutic approach to assist in the healing process in patients with diabetes mellitus.